(untitled) (AYUSHDHARA, 2022)
India’s domestic herb market is represented by very wide range of users from pharmaceutical industries; folk practitioners to house hold users. The herb market is very much complex by itself. As per WHO, 25% of the drugs tested use or other kind of herbs, with advent of social media and information age, people all over the world are better informed about usefulness and safety. The domestic market of Indian system of medicines & Homeopathy (ISM&H) is of the order of Rs4000 Crore with total consumption of all botanicals to figure of 17,700MT which is expanding day by day. The annual turnover of the Ayurvedic drug manufacturing industry is estimated around Rs3,500 Crore. Due to high demand all over the world, the genuinity of drugs and the natural resources are threatened. To overcome the issue, Government of India has taken several measures to promote the cultivation of medicinal plants. It will be of help in conservation of natural resources and also to meet the demand of herb market with genuine articles. In this article, demand and supply, the dynamics, market segments, regional analysis, research articles on herb market, along with government initiative for cultivation and export of medicinal plants are reviewed and discussed